Learning in a noisy world: How lucky successes and unlucky failures shape learning consequences - Amanda Zaidan Chen; Martha Jeong; Michele Rigolizzo (PLoS ONE, 2026)
Learning is noisy. People can face unlucky failure , in which they fail despite using effective strategies, or experience lucky success , in which they succeed in spite of using suboptimal strategies. Both situations can serve as potentially valuable learning opportunities, as long as performance outcomes are interpreted accurately. This report examines people’s ability to recognize and adjust for these errors during the learning process. Our pilot data demonstrated that people assumed that noise affected failure at greater rates, and thereby believed successful outcomes were more informative learning cues. Based on these findings, our research aims to investigate whether experiencing a lucky success is more detrimental to future learning than experiencing unlucky failure, especially when it occurs at the beginning of a learning process. In other words, we seek to understand whether learners sufficiently discount the role of noise in successful outcomes or place too much weight on the informative value of their success, thereby hindering their learning when these outcomes are noisy.